Respuesta :

Answer:

f(x) = (x - 3)² - 6

Step-by-step explanation:

To complete the square, we need to subtract 3 from both sides first

f(x) = x² - 6x + 3

- 3                 - 3

f(x) - 3 = x² - 6x

Then add 9 to both sides since it is the square of half of b (6)

f(x) - 3 + 9 = x² - 6x + 9

f(x) + 6 = x² - 6x + 9

Factor the polynomial, x² - 6x + 9

f(x) + 6 = x² - 6x + 9

f(x) + 6 = (x - 3)(x - 3)

f(x) + 6 = (x - 3)²

Finally, subtract 6 from both sides

f(x) + 6 = (x - 3)²

     - 6        - 6

f(x) = (x - 3)² - 6

With this vertex form equation, we know the vertex is (3, -6)